Structure and the Compotition of Vegetation on the Permanent Plot in the Forest of the Jambi Mendalo University Campus - Nursanti Nursanti; Rizky Hardiyanti (Fakultas Kehutanan Universitas Jambi, 2020)
The Forest of the Jambi Mendalo University Campus is one of the green open spaces in the Jambi University Campus environment and in the City of Jambi which has many functions and potential to be developed. Its main function is the source of oxygen and CO2 absorbent in the campus environment, the source of biodiversity of the germplasm of Sumatra's lowland forest ecosystems and as a means of education for students, elementary school students to high schools and the people of the city of Jambi. Until now data about existing plant species and their potential is still very limited. Existing research is limited to carbon sequestration, the distribution patterns of several tree species and the physical conditions of their environment. The study was conducted in 2019. Sample plots in the form of a single plot measuring 160 x 60 meters were placed purposively at the study site. Based on the results of the inventory and identification, there were 176 species (species), 116 genera (genera) and 55 families (families). Still found species of the Dipterocarpaceae tribe, namely Shorea leprosula, Shorea parvifolia and Parashorea sp. Of the 109 species of stadia seedlings, 58 species are classified as saplings, 23 species of shrubs, 20 types of liana, 4 types of herbs, 2 types of ferns and 2 types of palm. Keywords: The forest of the campus, permanent sample plot, The compotition of vegetation